2022
DOI: 10.3389/fenvs.2022.879717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation patchiness on ecosystem carbon and nitrogen storage in the alpine grassland of the Qilian Mountains

Abstract: Vegetation patchiness is common in degraded grasslands. Vegetation patchiness enhances the spatial variability of grassland soil organic carbon and total nitrogen. Stripped vegetation patches have a great impact on ecosystem carbon (C) and nitrogen (N) storage. Using field surveys, we examined the effects of patches on the ecosystem carbon and nitrogen storage of four typical alpine grass species patches (viz: Leymus secalinus, Koeleria pers, Stipa aliena, and Leontopodium nanum). The results indicated that ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…For example, Abalori et al. (2022) indicated that the morphological traits of plants are most likely the primary cause of the variances in soil C and N storage and distribution among patches. Therefore, the formation of herbaceous patches may impair the C sequestration capacity of grassland ecosystems, which varies according to the dominant species in the patches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Abalori et al. (2022) indicated that the morphological traits of plants are most likely the primary cause of the variances in soil C and N storage and distribution among patches. Therefore, the formation of herbaceous patches may impair the C sequestration capacity of grassland ecosystems, which varies according to the dominant species in the patches.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly associated with variances in patch structure and the identity of their dominant species. For example,Abalori et al (2022) indicated that the morphological traits of plants are most likely the primary cause of the variances in soil C and N storage and distribution among patches. Therefore, the formation of herbaceous patches may impair the C sequestration capacity of grassland ecosystems, which varies according to the dominant species in the patches.5 | CON CLUS IONSAt the alpine meadow site of the present study, compared to the control, the L. secalinus, K. humilis, Leo.…”
mentioning
confidence: 99%